A five-element MAX phase ceramic material and preparation method thereof

Five-membered MAX phase material (ZrCrTi)AlC2) was prepared by vacuum hot press sintering, which solved the problem of lack of five-membered MAX phase material in the prior art, and achieved the preparation of ceramic materials with high density, excellent mechanical properties and electrical conductivity.

CN116947494BActive Publication Date: 2025-02-11HEFEI INNOVATION RES INST BEIHANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210412736.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-19
Publication Date
2025-02-11
Estimated Expiration
2042-04-19

AI Technical Summary

Technical Problem

There is a lack of research and preparation methods for five-membered MAX phase materials in the prior art, and most of the high-entropy multivariate MAX phase materials are disordered, and the conductivity and mechanical properties are insufficient.

Method used

The five-membered MAX phase material (ZrCrTi)AlC2) was prepared by vacuum hot press sintering method, and the denseness and structural regularity of the material were ensured through ball mill mixing, sieve powder, tableting and secondary sintering.

Benefits of technology

The prepared five-membered MAX-phase ceramic material has excellent mechanical properties and conductive properties, high density, high Vickers hardness, good fracture toughness and low resistivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116947494B_ABST
    Figure CN116947494B_ABST
Patent Text Reader

Abstract

The present invention discloses a five-element MAX phase ceramic material and a preparation method thereof. The molecular formula of the five-element MAX phase material is (ZrCrTi)AlC2. The raw materials including Zr powder, Cr powder, Ti powder, Al powder and C powder mixed powder are first ball-milled to prepare a uniformly mixed nanostructured mixed powder; the mixed powder is placed in a steel mold and pressed into a ceramic blank, and after molding, vacuum hot pressing and sintering is performed in a vacuum hot pressing furnace to prepare the ceramic blank. The (ZrCrTi)AlC2 ceramic material prepared by the present invention breaks through the quaternary restriction of the types of traditional MAX phase elements, and is different from the i-MAX in which the M (Zr, Cr, Ti) elements are mutually doped. The single element atoms form a layer by themselves, so it has higher hardness, toughness and strength, and has good machinability, while improving the conductivity of the five-element MAX phase ceramic material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of inorganic non-metallic conductive ceramics, and in particular relates to a quinary MAX phase ceramic material and a preparation method thereof. Background Art

[0002] MAX phase is a well-studied class of layered carbides, carbonitrides and nitrides, where M is a transition metal, A is a main group element Al or Si, and X represents C and / or N. The 3d orbital of the transition metal couples with the 2p orbital of A, making the MAX phase material have good conductivity, and thus is called conductive ceramic. The traditional ternary MAX phase crystallizes in the P63 / mmc hexagonal structure. Through alloying, the quaternary (M′M″) n+1 AlC n The MAX phases (Cr2TiAlC2, Mo2TiAlC2 and Mo2Ti2AlC3) were also experimentally synthesized in a hexagonal structure, where (M′ and M″ represent two different transition metal elements. In this hexagonal structure, the inner layer M″ is sandwiched by two outer layers M′, which are called o-MAX phases, and where n=2. Later, new quaternary MAX phases were synthesized. The V and Zr atoms are orderly arranged within a single M layer, which is called the i-MAX phase and represented as (Only for n=1) Previously, quinary MAX phase materials have not been reported, and high-entropy multi-component MAX phase materials are mostly i-MAX. Summary of the invention

[0003] In order to improve the above technical problems, the present invention proposes for the first time a five-element MAX phase material with a molecular formula of (ZrCrTi)AlC2 and a preparation method thereof, wherein pressed Zr powder, Cr powder, Ti powder, Al powder and C powder are pressed into tablets for hot pressing and sintering to generate (ZrCrTi)AlC2 ceramics. The mechanical properties and electrical conductivity of the five-element MAX phase material of the present invention are better than those of high entropy i-MAX ceramics.

[0004] The technical solution adopted by the present invention is as follows:

[0005] A quinary MAX phase material having the molecular formula (ZrCrTi)AlC2.

[0006] According to an embodiment of the present invention, the five-element MAX phase material is prepared from raw materials including a mixed powder of Zr powder, Cr powder, Ti powder, Al powder and C powder by vacuum hot pressing and sintering.

[0007] The present invention also provides a method for preparing the five-element MAX phase material, comprising using Zr powder, Cr powder, Ti powder, Al powder and C powder as raw materials, and preparing the five-element MAX phase material through a vacuum hot pressing sintering method.

[0008] According to an embodiment of the present invention, the molar ratio of the Zr powder, Cr powder, Ti powder, Al powder and C powder is 1:1:1:(1.0-1.3):(2.0-2.2), preferably 1:1:1:(1.05-1.15):(2.1-2.15), and exemplarily 1:1:1:1.1:2.1.

[0009] According to an embodiment of the present invention, the preparation method further comprises ball milling the Zr powder, Cr powder, Ti powder, Al powder and C powder. Preferably, the ball milling process is as follows: the ball-to-material ratio is (8-15):1, the rotation speed is 200-400 r / min, and the ball milling time is 10-15 h.

[0010] Preferably, the ball milling medium is a 0.2 mm agate ball.

[0011] According to an embodiment of the present invention, the preparation method further comprises sieving the mixed powder after ball milling, for example, using a standard 92A type vibrating sieving machine, and the particle size of the powder after sieving is 10-15 μm.

[0012] According to an embodiment of the present invention, the preparation method further comprises adding a grinding aid to the sieved mixed powder, grinding it, and drying it to obtain the mixed powder. Preferably, the selected grinding aid is anhydrous ethanol.

[0013] Preferably, the mass ratio of the grinding aid to the mixed powder is 0.6:1 to 1:1, exemplified by 0.6:1, 0.8:1, and 1:1.

[0014] According to an embodiment of the present invention, the preparation method further comprises tableting the dried mixed powder to obtain a ceramic blank. Preferably, the tableting pressure is 10-20 MPa and the pressure holding time is 2-10 min, exemplified by 2 min, 5 min, and 10 min.

[0015] According to an embodiment of the present invention, the vacuum hot pressing sintering method adopts a secondary sintering process;

[0016] The primary vacuum hot pressing sintering adopts a two-stage calcination treatment. The temperature of the primary vacuum hot pressing sintering is 600-700°C, exemplified by 600°C, 660°C, and 700°C; the holding time of the primary vacuum hot pressing sintering is 0.5-2h, exemplified by 0.5h, 1h, and 2h; the temperature of the secondary vacuum hot pressing sintering is 800-1000°C, exemplified by 800°C, 900°C, and 1000°C; the time of the secondary vacuum hot pressing sintering is 3-5h, exemplified by 3h, 4h, and 5h.

[0017] The secondary vacuum hot pressing sintering adopts a two-stage calcination treatment. The temperature of the first-stage vacuum hot pressing sintering is 900-1100°C, exemplified by 900°C, 1000°C, and 1100°C; the temperature of the second-stage vacuum hot pressing sintering is 1100-1300°C, exemplified by 1100°C, 1250°C, and 1300°C; the insulation time of the second-stage vacuum hot pressing sintering is 1-20h, exemplified by 1h, 10h, and 20h.

[0018] The vacuum degree of the secondary vacuum hot pressing sintering is 1×10 -1 ~2×10 -2 MPa, exemplified by 1×10 -2 MPa, 1.5×10 -2 MPa, 2×10 -2 MPa.

[0019] According to an embodiment of the present invention, in the vacuum hot pressing sintering method, the heating rates of the primary sintering and the secondary sintering are the same or different, and are independently 1 to 10°C / min, exemplified by 1°C / min, 5°C / min, and 10°C / min.

[0020] According to an embodiment of the present invention, the preparation method further comprises crushing the pressed tablet after the primary vacuum hot pressing sintering.

[0021] For example, the sintered mixed powder is placed in a planetary ball mill with a ball-to-material ratio of (8-15):1, a rotation speed of 300-400 r / min, and a time of 10-15 h; preferably, the ball-to-material ratio is 15:1, the rotation speed is 400 r / min, and the time is 10 h; and / or, a powder screening process is performed, the size of the sieve is 200-225 mesh, and the powder particles that cannot pass through the sieve are ground into powder using a mortar and then passed through the sieve to make the powder size 15 μm.

[0022] According to an embodiment of the present invention, the preparation method further comprises tableting the crushed powder. Preferably, the tableting pressure is 30-50 MPa, exemplarily 50 MPa.

[0023] According to an embodiment of the present invention, the method for preparing the quinary MAX phase material comprises the following steps:

[0024] S1, ball-milling Zr powder, Cr powder, Ti powder, Al powder and C powder, sieving the powder, adding a grinding aid, grinding and drying to obtain a mixed powder;

[0025] S2, pressing the mixed powder prepared in step S1 to obtain a MAX phase embryo; placing the mixed powder in a vacuum hot pressing sintering furnace for a vacuum hot pressing sintering, keeping the mixture at the highest temperature, and then cooling the mixture naturally;

[0026] S3, re-grinding and pressing the pressed tablets after the first vacuum hot pressing sintering in step S2, and performing a second vacuum hot pressing sintering in a vacuum hot pressing sintering furnace; cooling after the second vacuum hot pressing sintering to obtain the five-element MAX phase ceramic material.

[0027] Beneficial effects of the present invention:

[0028] Inspired by the transformation from ternary MAX phase to quaternary MAX phase, the present invention prepares a quinary MAX phase material and a preparation method thereof. Specifically:

[0029] The present invention uses vacuum hot pressing sintering to prepare quinary MAX phase ceramics. On the one hand, it is to reduce the contamination of impurity gases (such as oxygen and nitrogen) to the material; on the other hand, hot pressing can make the pressure transmission more sufficient, thereby making the structure of the obtained ceramic phase denser, so as to obtain good mechanical properties.

[0030] The present invention adopts the method of vacuum hot pressing sintering to prepare the five-element MAX phase material, which enriches the types of MAX phase materials. Compared with the multi-element high entropy MAX phase, the five-element MAX phase material of the present invention has a better ordered type, a relatively regular organizational structure, a small number of impurity atoms and a small lattice distortion, a low residual resistivity and good conductivity (such as the ordered (Cr 2 / 3 Ti 1 / 3 )3AlC2 has a resistivity of 0.31μΩm, while disordered (Cr x Ti 1-x ) The resistivity of 3AlC2 is 0.68μΩm). At the same time, the strong covalent bonds between the MX of the quinary MAX phase material of the present invention and the strong covalent bonds between the ordered M layer and the A layer improve its strength and toughness. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the SEM photograph of the room temperature fracture of the (ZrCrTi)AlC2 quinary MAX phase ceramic material prepared in Comparative Example 1.

[0032] Figure 2 This is a SEM photograph of the room temperature fracture of the (ZrCrTi)AlC2 quinary MAX phase ceramic material prepared in Example 1.

[0033] Figure 3 This is the SEM photograph of the room temperature fracture of the (ZrCrTi)AlC2 quinary MAX phase ceramic material prepared in Example 2. DETAILED DESCRIPTION

[0034] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0035] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0036] In the following embodiments and comparative examples of the present invention, the density test was performed by the Archimedes method, the Vickers hardness test was performed according to the GB / T4340-2009 standard, the fracture toughness test was performed according to the GB / T 21143-2014 standard, and the resistivity was measured by the four-probe resistivity method according to the GB / T 21143-2014 standard.

[0037] Comparative Example 1

[0038] The preparation method of the quinary MAX phase material comprises the following steps:

[0039] The ball milling step before the primary vacuum sintering is as follows: Zr powder, Cr powder, Ti powder, Al powder and C powder are mixed by ball milling in a ratio of 1:1:1:1:2, the ball milling process is as follows: the ball-to-material ratio is 15:1, the rotation speed is 400 r / min, the ball milling time is 15 h, and the ball milling medium is a 0.2 mm agate ball;

[0040] Powder screening step: Use a standard 92A type vibration sieving machine, and the powder particle size after screening is 10-15μm;

[0041] Tableting step: prepare a Φ19.80mm steel mold, spray BN coating on the inner wall of the mold and the surface of the pressing head, place the mixed powder obtained after screening in the steel mold, load the pressure at 15MPa, and hold the pressure for 5min to obtain a ceramic blank;

[0042] The first vacuum sintering step is as follows: prepare a Φ20mm graphite mold and embed a carbon paper with a thickness of 0.2mm, place the obtained ceramic embryo in the graphite mold, and sinter in a vacuum hot pressing sintering furnace. The sintering method is as follows: evacuate the sintering furnace to below 20Pa at room temperature, increase the temperature to 660℃ at a heating rate of 5℃ / min, keep it warm for 1h, load the pressure to 5MPa, then increase the temperature to 900℃ at a heating rate of 3℃ / min, keep it warm for 4h, load the pressure to 10MPa, and immediately reduce the pressure and temperature after the insulation is completed. The sample is cooled with the furnace to finally prepare the (ZrCrTi)AlC2 ceramic material.

[0043] Figure 1This is a SEM photograph of the room temperature fracture of the (ZrCrTi)AlC2 five-element MAX phase ceramic material prepared in Comparative Example 1. From the figure, it can be seen that the (ZrCrTi)AlC2 five-element MAX phase ceramic material prepared in this comparative example is a flaky structure, but contains fine Al particles inside, which indicates that a large amount of liquid phase is generated during the primary vacuum sintering, and the temperature is relatively low, so that Al is not inserted into the flaky layer.

[0044] After testing, the (ZrCrTi)AlC2 ceramic material prepared in Comparative Example 1 has a density of 95.4%, a Vickers hardness of 7.2 GPa, a fracture toughness of 7.1 MPa·m, and a resistivity of 0.63 μΩm.

[0045] Example 1

[0046] The preparation method of the quinary MAX phase material comprises the following steps:

[0047] The ball milling step before the primary sintering is as follows: Zr powder, Cr powder, Ti powder, Al powder and C powder are mixed by ball milling in a ratio of 1:1:1:1:2, the ball-to-material ratio is 15:1, the rotation speed is 400 r / min, the ball milling time is 15 h, and the ball milling medium is a 0.2 mm agate ball;

[0048] Powder screening step: Use a standard 92A type vibration sieving machine, and the powder particle size after screening is 10-15μm;

[0049] Tableting step: prepare a Φ19.80mm steel mold, spray BN coating on the inner wall of the mold and the surface of the pressing head, place the mixed powder obtained after screening in the steel mold, load the pressure at 15MPa, and hold the pressure for 5min to obtain a ceramic blank;

[0050] The first sintering step is as follows: prepare a Φ20mm graphite mold and embed a carbon paper with a thickness of 0.2mm, place the obtained ceramic blank in the graphite mold, and sinter in a vacuum hot pressing sintering furnace. The sintering method is as follows: evacuate the sintering furnace to below 20Pa at room temperature, increase the temperature to 660℃ at a heating rate of 5℃ / min, keep it warm for 1h, load the pressure of 5MPa, and then increase the temperature to 900℃ at a heating rate of 3℃ / min, keep it warm for 4h, load the pressure of 10MPa, and immediately reduce the pressure and temperature after the insulation is completed. The sample is cooled with the furnace to obtain the sintered five-element MAX pressed tablet (ZrCrTi)AlC2;

[0051] The sintered five-element MAX tablets were crushed in an agate mortar, and the mixed powders were put into a planetary ball mill with a ball-to-material ratio of 15:1, a rotation speed of 400r / min, and a time of 10h; the powders were sieved with a 225-mesh sieve, and the powder particles that could not pass through the sieve were ground into powder with a mortar, and then passed through the sieve to make the powder size 15μm;

[0052] The mixed powder was placed in a 19.80 mm steel die and pressed, BN coating was sprayed on the surface of the press head, a pressure of 50 MPa was applied, and pressing was performed twice;

[0053] The tablet was placed in a vacuum hot pressing furnace with a Φ20 mm graphite mold. The initial heating rate of the secondary sintering was 5 °C / min to 1000 °C, the pressure was 15 MPa, and the vacuum degree was 2 × 10 -2 Pa; after reaching 1000°C, the temperature was raised to 1250°C at a rate of 2°C / min, pressurized to 55MPa, kept warm for 10h, and then naturally cooled to room temperature to finally prepare (ZrCrTi)AlC2 ceramic material.

[0054] Figure 2 This is a SEM photograph of the room temperature fracture of the (ZrCrTi)AlC2 five-element MAX phase ceramic material prepared in Example 1. From the figure, it can be seen that the (ZrCrTi)AlC2 five-element MAX phase ceramic material prepared in this example has a layered structure and a small particle size, so that the prepared (ZrCrTi)AlC2 five-element MAX phase ceramic material has excellent mechanical properties and electrical conductivity.

[0055] After testing, the density of the (ZrCrTi)AlC2 quinary MAX phase ceramic material prepared in Example 1 is 99.1%, the Vickers hardness is 11.5 GPa, the fracture toughness is 6.3 MPa·m, and the resistivity is 0.26 μΩm.

[0056] Comparative Example 2

[0057] The preparation method of the quinary MAX phase material comprises the following steps:

[0058] The ball milling step before the primary sintering is as follows: Zr powder, Cr powder, Ti powder, Al powder and C powder are mixed by ball milling in a ratio of 1:1:1:1.1:2.1. The ball milling process is as follows: the ball-to-material ratio is 15:1, the rotation speed is 400 r / min, the ball milling time is 15 h, and the ball milling medium is a 0.2 mm agate ball;

[0059] Powder screening step: Use a standard 92A type vibration sieving machine, and the powder particle size after screening is 10-15μm;

[0060] Tableting step: prepare a Φ19.80mm steel mold, spray BN coating on the inner wall of the mold and the surface of the pressing head, place the mixed powder obtained after screening in the steel mold, load the pressure at 15MPa, and hold the pressure for 5min to obtain a ceramic blank;

[0061] The first sintering step is as follows: prepare a Φ20mm graphite mold and embed a carbon paper with a thickness of 0.2mm. Place the obtained ceramic embryo in the graphite mold and sinter it in a vacuum hot pressing sintering furnace. The sintering method is as follows: evacuate the sintering furnace to below 20Pa at room temperature, increase the temperature to 660℃ at a heating rate of 5℃ / min, keep it warm for 1h, load the pressure to 5MPa, then increase the temperature to 900℃ at a heating rate of 3℃ / min, keep it warm for 5h, load the pressure to 10MPa, and immediately reduce the pressure and temperature after the insulation is completed. The sample is cooled with the furnace to finally prepare the (ZrCrTi)AlC2 ceramic material.

[0062] After testing, the (ZrCrTi)AlC prepared in Comparative Example 2 22 The density of the quinary MAX phase ceramic material is 96.7%, the Vickers hardness is 7.8 GPa, the fracture toughness is 6.6 MPa·m, and the resistivity is 0.58 μΩm.

[0063] Example 2

[0064] The preparation method of the quinary MAX phase material comprises the following steps:

[0065] The ball milling step before the primary sintering is as follows: Zr powder, Cr powder, Ti powder, Al powder and C powder are mixed by ball milling in a ratio of 1:1:1:1.1:2.1. The ball milling process is as follows: the ball-to-material ratio is 15:1, the rotation speed is 400 r / min, the ball milling time is 15 h, and the ball milling medium is a 0.2 mm agate ball;

[0066] Powder screening step: Use a standard 92A type vibration sieving machine, and the powder particle size after screening is 10-15μm;

[0067] Tableting step: prepare a Φ19.80mm steel mold, spray BN coating on the inner wall of the mold and the surface of the pressing head, place the mixed powder obtained after screening in the steel mold, load the pressure to 15MPa, and hold the pressure for 5min to obtain a ceramic blank;

[0068] The first sintering step is as follows: prepare a Φ20mm graphite mold and embed a carbon paper with a thickness of 0.2mm, place the obtained ceramic blank in the graphite mold, and sinter in a vacuum hot pressing sintering furnace. The sintering method is as follows: evacuate the sintering furnace to below 20Pa at room temperature, increase the temperature to 660℃ at a heating rate of 5℃ / min, keep it warm for 1h, load the pressure of 5MPa, and then increase the temperature to 900℃ at a heating rate of 3℃ / min, keep it warm for 5h, load the pressure of 10MPa, and immediately reduce the pressure and temperature after the insulation is completed. The sample is cooled with the furnace to obtain the sintered five-element MAX pressed tablet (ZrCrTi)AlC2;

[0069] The sintered five-element MAX tablets were crushed in an agate mortar, and the mixed powders were put into a planetary ball mill with a ball-to-material ratio of 15:1, a rotation speed of 400r / min, and a time of 10h; the powders were sieved with a 225-mesh sieve, and the powder particles that could not pass through the sieve were ground into powder with a mortar, and then passed through the sieve to make the powder size 15μm;

[0070] The mixed powder was placed in a 19.80 mm steel die and pressed, BN coating was sprayed on the surface of the press head, a pressure of 50 MPa was applied, and pressing was performed twice;

[0071] The tablet was placed in a vacuum hot pressing furnace with a Φ20 mm graphite mold. The initial heating rate of the secondary sintering was 5 °C / min to 1000 °C, the pressure was 15 MPa, and the vacuum degree was 2 × 10 -2 Pa; after reaching 1000°C, the temperature was raised to 1250°C at a rate of 2°C / min, pressurized to 55MPa, kept warm for 10h, and then naturally cooled to room temperature to finally prepare (ZrCrTi)AlC2 ceramic material.

[0072] Figure 3 This is a SEM photo of the room temperature fracture of the (ZrCrTi)AlC2 five-element MAX phase ceramic material prepared in Example 2. From the figure, it can be seen that the (ZrCrTi)AlC2 five-element MAX phase ceramic material prepared in this example has a layered structure, with a high number of stacking layers and a large particle size. Therefore, the prepared (ZrCrTi)AlC2 five-element MAX phase ceramic material has good electrical conductivity.

[0073] After testing, the (ZrCrTi)AlC prepared in Example 2 22 The density of the quinary MAX phase ceramic material is 99.3%, the Vickers hardness is 12.4 GPa, the fracture toughness is 5.8 MPa·m, and the resistivity is 0.23 μΩm.

[0074] Example 3

[0075] The preparation method of the quinary MAX phase material comprises the following steps:

[0076] The ball milling step before the primary sintering is as follows: Zr powder, Cr powder, Ti powder, Al powder and C powder are mixed by ball milling in a ratio of 1:1:1:1.1:2.1. The ball milling process is as follows: the ball-to-material ratio is 10:1, the rotation speed is 300 r / min, the ball milling time is 10 h, and the ball milling medium is a 0.2 mm agate ball;

[0077] Powder screening step: Use a standard 92A type vibration sieving machine, and the powder particle size after screening is 10-15μm;

[0078] Tableting step: prepare a Φ19.80mm steel mold, spray BN coating on the inner wall of the mold and the surface of the pressing head, place the mixed powder obtained after screening in the steel mold, load the pressure at 15MPa, and hold the pressure for 5min to obtain a ceramic blank;

[0079] The first sintering step is as follows: prepare a Φ20mm graphite mold and embed a carbon paper with a thickness of 0.2mm, place the obtained ceramic blank in the graphite mold, and sinter in a vacuum hot pressing sintering furnace. The sintering method is as follows: evacuate the sintering furnace to below 20Pa at room temperature, increase the temperature to 660℃ at a heating rate of 5℃ / min, keep it warm for 1h, and apply a pressure of 5MPa, then increase the temperature to 1000℃ at a heating rate of 4℃ / min, keep it warm for 5h, apply a pressure of 10MPa, and apply a pressure of 10MPa. After the temperature is over, the pressure and temperature are immediately reduced, and the sample is cooled with the furnace to obtain the sintered five-element MAX tablets; (ZrCrTi)AlC2 The sintered five-element MAX tablets are crushed in an agate mortar, and the mixed powder is put into a planetary ball mill with a ball-to-material ratio of 15:1, a rotation speed of 400r / min, and a time of 15h; It is sieved with a 225-mesh screen. For the powder particles that cannot pass through the screen, the powder is ground into powder with a mortar, and then passed through the screen to make the powder size 15μm;

[0080] The mixed powder was placed in a 19.80 mm steel die and pressed, BN coating was sprayed on the surface of the press head, a pressure of 50 MPa was applied, and pressing was performed twice;

[0081] The tablet was placed in a vacuum hot pressing furnace with a Φ20 mm graphite mold. The initial heating rate of the secondary sintering was 5 °C / min to 1000 °C, the pressure was 15 MPa, and the vacuum degree was 2 × 10 -2 Pa; after reaching 1000°C, the temperature was raised to 1300°C at a rate of 2°C / min, pressurized to 55MPa, kept warm for 20h, and then naturally cooled to room temperature to finally prepare (ZrCrTi)AlC2 ceramic material.

[0082] After testing, the density of the (ZrCrTi)AlC2 quinary MAX phase ceramic material prepared in Example 3 is 98.4%, the Vickers hardness is 10.5 GPa, the fracture toughness is 6.6 MPa·m, and the resistivity is 0.28 μΩm.

[0083] Example 4

[0084] The preparation method of the quinary MAX phase material comprises the following steps:

[0085] The ball milling step before the primary sintering is as follows: Zr powder, Cr powder, Ti powder, Al powder and C powder are mixed by ball milling in a ratio of 1:1:1:1.15:2.15. The ball milling process is as follows: the ball-to-material ratio is 10:1, the rotation speed is 300 r / min, the ball milling time is 10 h, and the ball milling medium is a 0.2 mm agate ball;

[0086] Powder screening step: Use a standard 92A type vibration sieving machine, and the powder particle size after screening is 10-15μm;

[0087] Tableting step: prepare a Φ19.80mm steel mold, spray BN coating on the inner wall of the mold and the surface of the pressing head, place the mixed powder obtained after screening in the steel mold, load the pressure to 15MPa, and hold the pressure for 5min to obtain a ceramic blank;

[0088] The first sintering step is as follows: prepare a Φ20mm graphite mold and embed a carbon paper with a thickness of 0.2mm, place the obtained ceramic blank in the graphite mold, and sinter in a vacuum hot pressing sintering furnace. The sintering method is as follows: evacuate the sintering furnace to below 20Pa at room temperature, increase the temperature to 660℃ at a heating rate of 5℃ / min, keep it warm for 1h, load the pressure of 5MPa, and then increase the temperature to 900℃ at a heating rate of 3℃ / min, keep it warm for 5h, load the pressure of 10MPa, and immediately reduce the pressure and temperature after the end of the insulation. The sample is cooled with the furnace to obtain the sintered five-element MAX pressed tablet; (ZrCrTi)AlC2

[0089] The sintered five-element MAX tablets were crushed in an agate mortar, and the mixed powders were put into a planetary ball mill with a ball-to-material ratio of 15:1, a rotation speed of 400r / min, and a time of 10h; the powders were sieved with a 225-mesh sieve, and the powder particles that could not pass through the sieve were ground into powder with a mortar, and then passed through the sieve to make the powder size 15μm;

[0090] The mixed powder was placed in a 19.80 mm steel die and pressed, BN coating was sprayed on the surface of the press head, a pressure of 50 MPa was applied, and pressing was performed twice;

[0091] The tablet was placed in a vacuum hot pressing furnace with a Φ20 mm graphite mold. The initial heating rate of the secondary sintering was 5 °C / min to 1000 °C, and the pressure was 15 MPa, 2 × 10 -2 Pa; after reaching 1000°C, the temperature was raised to 1250°C at a rate of 2°C / min, pressurized to 55MPa, kept warm for 10h, and then naturally cooled to room temperature to finally prepare (ZrCrTi)AlC2 ceramic material.

[0092] After testing, the density of the (ZrCrTi)AlC2 quinary MAX phase ceramic material prepared in Example 4 is 98.7%, the Vickers hardness is 10.8 GPa, the fracture toughness is 6.4 MPa·m, and the resistivity is 0.31 μΩm.

[0093] Comparative Example 3

[0094] The preparation method of the quinary MAX phase material comprises the following steps:

[0095] The ball milling step before the primary sintering is as follows: ZrC powder, Cr powder, Ti powder, Al powder and C powder are mixed by ball milling in a ratio of 1:1:1:1.1:1.1. The ball milling process is as follows: the ball-to-material ratio is 10:1, the rotation speed is 300 r / min, the ball milling time is 10 h, and the ball milling medium is a 0.2 mm agate ball;

[0096] Powder screening step: Use a standard 92A type vibration sieving machine, and the powder particle size after screening is 10-15μm;

[0097] Tableting step: prepare a Φ19.80mm steel mold, spray BN coating on the inner wall of the mold and the surface of the pressing head, place the mixed powder obtained after screening in the steel mold, load the pressure to 15MPa, and hold the pressure for 5min to obtain a ceramic blank;

[0098] The first sintering step is as follows: prepare a Φ20mm graphite mold and embed a carbon paper with a thickness of 0.2mm, place the obtained ceramic blank in the graphite mold, and sinter in a vacuum hot pressing sintering furnace. The sintering method is as follows: evacuate the sintering furnace to below 20Pa at room temperature, increase the temperature to 660℃ at a heating rate of 5℃ / min, keep it warm for 1h, and load a pressure of 5MPa, then increase the temperature to 900℃ at a heating rate of 3℃ / min, keep it warm for 5h, and load a pressure of 10MPa. After the insulation is completed, the pressure and temperature are immediately reduced, and the sample is cooled with the furnace to obtain the sintered five-element MAX pressed tablet;

[0099] The sintered five-element MAX tablets were crushed in an agate mortar, and the mixed powders were put into a planetary ball mill with a ball-to-material ratio of 15:1, a rotation speed of 400r / min, and a time of 10h; the powders were sieved with a 225-mesh sieve, and the powder particles that could not pass through the sieve were ground into powder with a mortar, and then passed through the sieve to make the powder size 15μm;

[0100] The mixed powder was placed in a 19.80 mm steel die and pressed, BN coating was sprayed on the surface of the press head, a pressure of 50 MPa was applied, and pressing was performed twice;

[0101] The tablet was placed in a vacuum hot pressing furnace with a Φ20 mm graphite mold. The initial heating rate of the secondary sintering was 5 °C / min to 1000 °C, and the pressure was 15 MPa, 2 × 10 -2Pa; after reaching 1000°C, the temperature was raised to 1250°C at a rate of 2°C / min, pressurized to 55MPa, kept warm for 10h, and then naturally cooled to room temperature to finally prepare (ZrCrTi)AlC2 ceramic material.

[0102] After testing, the density of the (ZrCrTi)AlC2 quinary MAX phase ceramic material prepared in Comparative Example 3 is 99.0%, the Vickers hardness is 8.9 GPa, the fracture toughness is 5.4 MPa·m, and the resistivity is 0.41 μΩm.

[0103] Comparative Example 4

[0104] The preparation method of the quinary MAX phase material comprises the following steps:

[0105] The ball milling step before the primary sintering is as follows: Zr powder, Cr powder, TiAl alloy powder and C powder are mixed by ball milling in a ratio of 1:1:1.1:2.1. The ball milling process is as follows: the ball-to-material ratio is 10:1, the rotation speed is 300 r / min, the ball milling time is 10 h, and the ball milling medium is a 0.2 mm agate ball;

[0106] Powder screening step: Use a standard 92A type vibration sieving machine, and the powder particle size after screening is 10-15μm;

[0107] Tableting step: prepare a Φ19.80mm steel mold, spray BN coating on the inner wall of the mold and the surface of the pressing head, place the mixed powder obtained after screening in the steel mold, load the pressure to 15MPa, and hold the pressure for 5min to obtain a ceramic blank;

[0108] The first sintering step is as follows: prepare a Φ20mm graphite mold and embed a carbon paper with a thickness of 0.2mm, place the obtained ceramic blank in the graphite mold, and sinter in a vacuum hot pressing sintering furnace. The sintering method is as follows: evacuate the sintering furnace to below 20Pa at room temperature, increase the temperature to 660℃ at a heating rate of 5℃ / min, keep it warm for 1h, and load a pressure of 5MPa, then increase the temperature to 900℃ at a heating rate of 3℃ / min, keep it warm for 5h, and load a pressure of 10MPa. After the insulation is completed, the pressure and temperature are immediately reduced, and the sample is cooled with the furnace to obtain the sintered five-element MAX pressed tablet;

[0109] The sintered five-element MAX tablets were crushed in an agate mortar, and the mixed powders were put into a planetary ball mill with a ball-to-material ratio of 15:1, a rotation speed of 400r / min, and a time of 10h; the powders were sieved with a 225-mesh sieve, and the powder particles that could not pass through the sieve were ground into powder with a mortar, and then passed through the sieve to make the powder size 15μm;

[0110] The mixed powder was placed in a 19.80 mm steel die and pressed, BN coating was sprayed on the surface of the press head, a pressure of 50 MPa was applied, and pressing was performed twice;

[0111] The tablet was placed in a vacuum hot pressing furnace with a Φ20 mm graphite mold. The initial heating rate of the secondary sintering was 5 °C / min to 1000 °C, and the pressure was 15 MPa, 2 × 10 -2 Pa; after reaching 1000°C, the temperature was raised to 1350°C at a rate of 2°C / min, pressurized to 55MPa, kept warm for 10 hours, and then naturally cooled to room temperature to finally prepare (ZrCrTi)AlC2 ceramic material.

[0112] After testing, the density of the (ZrCrTi)AlC2 quinary MAX phase ceramic material prepared in Comparative Example 4 is 98.8%, the Vickers hardness is 10.0 GPa, the fracture toughness is 5.6 MPa·m, and the resistivity is 0.32 μΩm.

[0113] The performance results of the quinary MAX phase ceramic materials prepared in each embodiment and comparative example obtained by testing are shown in Table 1 below.

[0114] Table 1

[0115]

[0116]

[0117] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A five-element MAX phase material, characterized in that: Its molecular formula is (ZrCrTi)AlC2; the five-element MAX phase material is prepared from raw materials including mixed powders of Zr powder, Cr powder, Ti powder, Al powder and C powder by vacuum hot pressing sintering method; The vacuum hot pressing sintering method adopts a secondary sintering process; The primary vacuum hot pressing sintering adopts a two-stage calcination treatment: the temperature of the primary vacuum hot pressing sintering is 600~700℃, the holding time of the primary vacuum hot pressing sintering is 0.5~2h, the temperature of the secondary vacuum hot pressing sintering is 800~1000℃, and the holding time of the secondary vacuum hot pressing sintering is 3-5h; The secondary vacuum hot pressing sintering adopts a two-stage calcination treatment: the temperature of the first-stage vacuum hot pressing sintering is 900~1100℃, the temperature of the second-stage vacuum hot pressing sintering is 1100~1300℃, and the insulation time of the second-stage vacuum hot pressing sintering is 1-20h.

2. The method for preparing the quinary MAX phase material according to claim 1, characterized in that: The preparation method comprises using Zr powder, Cr powder, Ti powder, Al powder and C powder as raw materials, and preparing the five-element MAX phase material through vacuum hot pressing sintering; The vacuum hot pressing sintering method adopts a secondary sintering process; The primary vacuum hot pressing sintering adopts a two-stage calcination treatment: the temperature of the primary vacuum hot pressing sintering is 600~700℃, the holding time of the primary vacuum hot pressing sintering is 0.5~2h, the temperature of the secondary vacuum hot pressing sintering is 800~1000℃, and the holding time of the secondary vacuum hot pressing sintering is 3-5h; The secondary vacuum hot pressing sintering adopts a two-stage calcination treatment: the temperature of the first-stage vacuum hot pressing sintering is 900~1100℃, the temperature of the second-stage vacuum hot pressing sintering is 1100~1300℃, and the insulation time of the second-stage vacuum hot pressing sintering is 1-20h.

3. The preparation method according to claim 2, characterized in that The molar ratio of the Zr powder, Cr powder, Ti powder, Al powder and C powder is 1:1:1:(1.0-1.3):(2.0-2.2).

4. The preparation method according to claim 2, characterized in that: The preparation method further comprises ball milling and mixing Zr powder, Cr powder, Ti powder, Al powder and C powder.

5. The preparation method according to claim 4, characterized in that: The ball milling process is as follows: the ball-to-material ratio is (8-15):1, the rotation speed is 200-400 r / min, and the ball milling time is 10-15 hours.

6. The preparation method according to any one of claims 2 to 5, characterized in that: The preparation method further comprises sieving the mixed powder after ball milling; The preparation method further comprises adding a grinding aid to the sieved mixed powder, grinding it, and drying it to obtain the mixed powder; The mass ratio of the grinding aid to the mixed powder is 0.6:1~1:

1.

7. The preparation method according to claim 6, characterized in that: The preparation method further comprises tableting the dried mixed powder to obtain a ceramic blank.

8. The preparation method according to claim 7, characterized in that: The tabletting pressure is 10-20 MPa, and the pressure holding time is 2-10 min.

9. The preparation method according to any one of claims 2 to 5, characterized in that: The preparation method further comprises crushing the pressed tablet after the primary vacuum hot pressing sintering; The preparation method further comprises tableting the crushed powder, wherein the tableting pressure is 30-50 MPa.

10. The preparation method according to any one of claims 2 to 5, characterized in that: The preparation method of the five-element MAX phase material comprises the following steps: S1, ball-milling Zr powder, Cr powder, Ti powder, Al powder and C powder, sieving the powder, adding a grinding aid, grinding and drying to obtain a mixed powder; S2, pressing the mixed powder prepared in step S1 to obtain a MAX phase embryo; placing the mixed powder in a vacuum hot pressing sintering furnace for a vacuum hot pressing sintering, keeping the mixture at the highest temperature, and then cooling the mixture naturally; S3, re-grinding and pressing the pressed tablets after the first vacuum hot pressing sintering in step S2, and performing a second vacuum hot pressing sintering in a vacuum hot pressing sintering furnace; cooling after the second vacuum hot pressing sintering to obtain the five-element MAX phase ceramic material.

Citation Information

Patent Citations

  • Novel five-membered layered magnetic material, preparation method and application thereof

    CN111477419A

  • Sulfur-series medium-high entropy MAX phase solid solution material as well as preparation method and application of same

    CN112094121A